Unpaid dementia carers: a scoping review of the caregiving trajectory and changing short break needs - Caulfield, Maria; Seddon, Diane (Frontiers in Health Services, 2025)
IntroductionShort breaks are essential to enable unpaid carers to have a life alongside caregiving. However, there is limited understanding of how carers' break needs evolve over time. This scoping review aimed to identify models of dementia caregiving to explore how short break needs may change across the caregiving career.MethodsThe review followed the best practice guidelines by and Arksey and O'Malley and Levac et al. A search was conducted across four databases in 2023 and rerun in 2025: Applied Social Sciences Index and Abstracts, CINAHL, MEDLINE, and APA PsycINFO.ResultsEleven models were identified, outlining various stages of caregiving. These models focused specifically on spousal carers or predominantly included spouses. They demonstrate that caregiving is a dynamic process, marked by increasing demands on carers' time and shifting relational dynamics. The models suggest that short break needs may change in response to certain circumstances, with a shift in emphasis from relational well-being in the early stages to rest and recuperation in later stages.DiscussionThe findings highlight the importance of regular practitioner engagement to monitor and discuss changing break needs, and the need for accessible community and social opportunities that support a mutual respite experience for both the carer and the person with dementia. Key knowledge gaps are identified, including the potential role of short breaks in supporting the person with dementia during the transition to residential care, and in helping carers adjust to this new phase of caregiving. Future research could also examine the best ways to capture and monitor short break needs over time, including during Carers' Assessments and other short break conversations.